Riscos potenciais aos manguezais do litoral norte do estado de São Paulo na revisão do Zoneamento Ecológico-Econômico Costeiro - Oliva, Pedro Barboza (Universidade Federal de São Carlos, 2020)
Mangroves are extremely important ecosystems, both for nature cycles and for humans. They provide a series of benefits, such as maintenance of fishing resources, control of hydrological cycles, maintenance of water quality, stabilization of the coastline, sediment retention, scenic beauty, among others. They are situated by definition between terrestrial and marine environments, being covered and uncovered permanently by the tides, and may suffer impacts from both sides, such as through the sanitary sewage of upstream urban areas, or in oil spill by vessels at sea. This location, as privileged as it is fragile, can make it a symbol of the Coastal Zone, which in Brazil is considered by the Federal Constitution a national heritage. In this country, the National Coastal Management Plan aims to organize this part of the territory, involving both land and ocean and the transition ecosystems between them, seeking economic and social development linked to environmental conservation that guarantees human activities as their own and life quality of the population. These objectives can be achieved with the Coastal Ecological-Economic Zoning, instrument incorporated in the legislation to order the territory, directing how and where different human activities can be developed, as well as determining forms of environmental conservation. Its formatting is so relevant that the knowledge of which areas are subject to urbanization, and which degraded areas need to be reforested, or also which places allow fishing or installation of port structures. Thus, this public policy has a fundamental role in the conservation of mangroves. This research aims to verify whether the review process of the Coastal Ecological-Economic Zoning of the North Coast of São Paulo, completed in 2017, increased or decreased in relation to the previous version of 2004 the protection of the mangroves in the region. For that, the two versions were compared considering both their texts and maps, as they are inseparable elements, as well as correlating with the use of the environments in 2016, and also with the future expectation of using the environments in both versions. The results show that the urban area tends to more than double, increasing the impacts that already exist in the mangroves due to the low coverage of public services infrastructure. Urban expansion is strongly directed towards extensive areas of native vegetation, which are expected to weaken the sensitive hydrological dynamics of mangroves, and the marine environment now has more permissible uses that can impact mangroves. The legislation that should be used in line with the Coastal Ecological- Economic Zoning to maintain the region's environmental quality has not been sufficiently observed, causing environmental degradation and the life quality of the population.
Potential risks to mangroves on the north coast of São Paulo state in Coastal Ecological-Economic Zoning review
Keywords: Zoneamento Ecológico-Economico Costeiro; Manguezal; Litoral Norte; Estado de São Paulo; Coastal Ecological-Economic Zoning; Mangrove; North Coast; São Paulo State; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL::LEGISLACAO AMBIENTAL